2022
DOI: 10.1111/jir.12954
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive cardiopulmonary profile of individuals with Down syndrome

Abstract: Background Individuals with Down syndrome (DS) have low levels of cardiorespiratory fitness and previous studies have shown that these low levels of fitness have a physiological cause. During exercise, the cardiovascular, ventilatory and muscular systems are simultaneously active. While individual parameters of these systems have been investigated in DS before, the interaction between these parameters and systems have not been discussed in detail. Doing so may provide important insight regarding the aetiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Despite what was mentioned above, these results are important, since there is controversy with the adaptations that can be achieved in this population, Bahiraei et al [72] mention that some exercise interventions may not achieve cardiorespiratory adaptations, mainly when looking for improvements in heart rate and VO2 maximum, arguing that the duration and intensity of the session are the main reasons for the difference in results. Furthermore, Beck et al [73] conclude that individuals with DS present cardiovascular, ventilatory, and muscular deterioration of the cardiopulmonary system, which could justify the difficulty of achieving adaptations in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Despite what was mentioned above, these results are important, since there is controversy with the adaptations that can be achieved in this population, Bahiraei et al [72] mention that some exercise interventions may not achieve cardiorespiratory adaptations, mainly when looking for improvements in heart rate and VO2 maximum, arguing that the duration and intensity of the session are the main reasons for the difference in results. Furthermore, Beck et al [73] conclude that individuals with DS present cardiovascular, ventilatory, and muscular deterioration of the cardiopulmonary system, which could justify the difficulty of achieving adaptations in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Age‐related increases in SB have been reported in the general population (Matthews et al, 2008), possibly due to age‐related decreases in physical fitness (Santos et al, 2012). Despite the lack of age‐related decreases in fitness observed in adults with DS (Baynard et al, 2008), greater amounts of SB among older individuals with DS may be due to underlying physiologic impairments in cardiorespiratory fitness (Beck et al, 2022). Therefore, adults with DS may engage in greater amounts of SB as they age and may lead to an increased risk for development of chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Down syndrome (DS) is caused by trisomy of the 21st chromosome (Bull, 2020). This genetic condition can produce physiologic impairment in cardiovascular, metabolic, and autonomic function (Beck et al, 2022; Fernhall et al, 2013; Moreau et al, 2021). It has been suggested that such physiologic impairment (Mahy et al, 2010) or environmental factors (Schultz et al, 2023) may be responsible for high amounts of sedentary behaviour (SB) that have been observed among adults with DS (Agiovlasitis et al, 2020; Oreskovic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Of these 45 tests, 41 used a treadmill protocol, and of those 41, the vast majority (29 out of 41) used a similar speed and incline protocol, all starting at an individualised walking speed at 0% incline, increasing the incline by 2.5% per step until 12.5% was reached, after which speed was increased until volitional exhaustion. These protocols did have minor variations in step duration: 21 protocols used 2-min steps (Baynard et al 2004;Fernhall et al 2005;Goulopoulou et al 2006;Baynard et al 2008;Cowley et al 2010;Cowley et al 2011;Ordonez et al 2014;Wee et al 2015;Boer & Moss 2016a,b;Boer 2017;Boer 2018;Mendonca et al 2018;Beck et al 2021;Oviedo et al 2021;Beck et al 2022;Oviedo et al 2022;Boer 2023;Dodd et al 2023), 1 protocol used 3-min steps (Climstein et al 1993), 4 protocols used 5-min steps until 7.5% incline and then 2-min steps from 7.5% to the end (Mendonca et al 2010;Mendonca et al 2010b;Mendonca et al 2011a,b), and 3 protocols used 4-min steps until 7.5% incline and 2-min steps from 7.5% to the end (Fernhall et al 2009;Mendonca et al 2022) (Climstein et al 1993).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The gold standard test for cardiorespiratory fitness is measuring peak oxygen uptake (VO 2 peak) during a maximal exercise test [American College of Sports Medicine (ACSM) 2022]. Maximal exercise testing has increasingly been applied to individuals with DS to investigate their response to acute and chronic exercise (Boer & Moss 2016a;Beck et al 2022;Oviedo et al 2022). The majority of these studies show a lower VO 2 peak in individuals with DS compared with the general population (Baynard et al 2008;Mendonca et al 2010b), although some other studies show a higher VO 2 peak in individuals with DS (Eberhard et al 1991).…”
Section: Introductionmentioning
confidence: 99%